Osteomyelitis Risk Factors Related to Combat Trauma Open Tibia Fractures: A Case–Control Analysis. Issue 9 (September 2018) - Tribble, David R.; Lewandowski, Louis R.; Potter, Benjamin K.; Petfield, Joseph L.; Stinner, Daniel J.; Ganesan, Anuradha; Krauss, Margot; Murray, Clinton K.
Abstract : Objectives: We assessed osteomyelitis risk factors in US military personnel with combat-related open tibia fractures (2003–2009). Methods: Patients with open tibia fractures who met the diagnostic criteria of osteomyelitis were identified as cases using Military Health System data and verified through medical record review. Controls were patients with open tibia fractures who did not meet osteomyelitis criteria. The Gustilo–Andersen fracture classification scheme was modified to include transtibial amputations (TTAs) as the most severe level. Logistic regression multivariable odds ratios [ORs; 95% confidence intervals (CI)] were assessed. Results: A total of 130 tibia osteomyelitis cases and 85 controls were identified. Excluding patients with TTAs, osteomyelitis cases had significantly longer time to radiographic union compared with controls (median: 210 vs. 165 days). Blast injuries, antibiotic bead utilization, ≥ Gustilo–Andersen-IIIb fractures [highest risk with TTA (OR: 15.10; CI: 3.22–71.07)], and foreign body at the fracture site were significantly associated with developing osteomyelitis. In a separate model, the Orthopaedic Trauma Association Open Fracture Classification muscle variable was significant with increasing risk from muscle loss (OR: 5.62; CI: 2.21–14.25) to dead muscle (OR: 8.46; CI: 3.31–21.64). When TTAs were excluded, significant risk factors were similar and included sustaining an injury between 2003 and 2006. Conclusions: Patients with severe blast trauma resulting in significant muscle damage are at the highest risk for osteomyelitis. The period association coincides with a time frame when several trauma system practice changes were initiated (eg, increased negative pressure wound therapy, decreased high-pressure irrigation, and reduced crystalloid use). Level of Evidence: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.